How do you solve x^3-x=1?

2 Answers
Apr 24, 2017

See below.

Explanation:

For my approach, I will be using a graphical interpretation.

You can rewrite the equation as x^3 - x - 1 = 0 as the first step.

Then graph the following: f(x) = x^3 - x - 1.

graph{x^3 - x - 1 [-10, 10, -5, 5]}

Click on where the graph intersects the x-axis. This point should be (1.325, 0). Therefore, the answer is x = 1.325.

Apr 24, 2017

Use Cardano's method to find real root:

x_1 = 1/3(root(3)((27+3sqrt(69))/2)+root(3)((27-3sqrt(69))/2))

color(white)(x_1) ~~ 1.324717957

and related complex roots.

Explanation:

Given:

x^3-x=1

Subtract 1 from both sides to get:

x^3-x-1 = 0

color(white)()
Discriminant

The discriminant Delta of a cubic polynomial in the form ax^3+bx^2+cx+d is given by the formula:

Delta = b^2c^2-4ac^3-4b^3d-27a^2d^2+18abcd

In our example, a=1, b=0, c=-1 and d=-1, so we find:

Delta = 0+4+0-27+0 = -23

Since Delta < 0 this cubic has 1 Real zero and 2 non-Real Complex zeros, which are Complex conjugates of one another.

color(white)()
Cardano's method

Let x = u+v.

Then our equation becomes:

(u+v)^3-(u+v)-1 = 0

Multiplying out and rearranging a little:

u^3+v^3+(3uv-1)(u+v)-1 = 0

Add the constraint v=1/(3u) to eliminate the term in (u+v) and get:

u^3+1/(27u^3)-1 = 0

Multiply through by 27u^3 to get:

27(u^3)^2-27(u^3)+1 = 0

Using the quadratic formula, we find:

u^3 = (27+-sqrt((-27)^2-4(27)(1)))/(2*27)

color(white)(u^3) = (27+-sqrt(729-108))/54

color(white)(u^3) = (27+-sqrt(621))/54

color(white)(u^3) = (27+-3sqrt(69))/54

Note that these values are both real and the derivation was symmetrical in u, v. So we can use one of these values for u^3 and the other for v^3 to find the real root:

x_1 = root(3)((27+3sqrt(69))/54)+root(3)((27-3sqrt(69))/54)

color(white)(x_1) = 1/3(root(3)((27+3sqrt(69))/2)+root(3)((27-3sqrt(69))/2))

color(white)(x_1) ~~ 1.324717957

The complex roots are given by multiplying u and v by suitable powers of omega=-1/2+sqrt(3)/2i, the primitive complex cube root of 1...

x_2 = 1/3(omega root(3)((27+3sqrt(69))/2)+omega^2 root(3)((27-3sqrt(69))/2))

x_3 = 1/3(omega^2 root(3)((27+3sqrt(69))/2)+omega root(3)((27-3sqrt(69))/2))